Collision of Cluster of Ions with the Surfaces - Hanon, Falah (University of Thi-Qar Journal of Science, 2013)
We study theoretically the collision between cluster of Pt and Pb ions with Al and graphite (HOPG) target in the ion incident range of energies within the range (200eV - 600eV) and the cluster of N (1- 10) ions.Using the rate equations, that describes the occupation numbers of the projectile and surface levels. Our results are in good agreement with experimental data.